Rat Cytomegalovirus Vaccine Prevents Accelerated Chronic Rejection in CMV‐Naïve Recipients of Infected Donor Allograft Hearts. Issue 7 (12th March 2015) - Streblow, D. N.; Hwee, Y. K.; Kreklywich, C. N.; Andoh, T.; Denton, M.; Smith, P.; Hart, E.; Broekel, R.; Pallett, C.; Rogers, K.; Streblow, A. D.; Chuop, M.; et al.
<x xml:space="preserve">Abstract</x> Cytomegalovirus accelerates transplant vascular sclerosis (TVS) and chronic rejection (CR) in solid organ transplants; however, the mechanisms involved are unclear. We determined the efficacy of a CMV vaccine in preventing CMV‐accelerated rat cardiac allograft rejection in naïve recipients of CMV+ donor hearts. F344 donor rats were infected with RCMV 5 days prior to heterotopic cardiac transplantation into CMV‐naïve or H2O2‐inactivated RCMV‐vaccinated Lewis recipients. Recipients of RCMV‐infected donor hearts rejected at POD59, whereas vaccinated recipients exhibited a significantly prolonged time to rejection‐POD97, similar to recipients of uninfected donor hearts (POD108). Although all of the donor hearts were preinfected, the vaccinated recipients had lower graft and PBMC viral loads at POD 7 compared to unvaccinated controls. Adoptive T cell and passive antibody transfers from vaccinated Lewis rats into naïve recipients demonstrate that both T‐cell and B‐cell arms of the adaptive immune response provide protection against CMV‐accelerated rejection. Similar findings were obtained when testing three different adjuvants in passive transfer experiments. We have determined that the timing of the vaccine prior to transplantation and the specific adjuvant play critical roles in mediating anti‐viral responses and promoting graft survival. CMV vaccination prior to transplantation may effectively increase graft survival.